2005
DOI: 10.1007/s10886-005-5288-z
|View full text |Cite
|
Sign up to set email alerts
|

Preformed and Induced Chemical Resistance of Tea Leaf Against Exobasidium vexans Infection

Abstract: Levels of (-)-epicatechin in tea cultivars (Camellia sinensis) resistant to blister blight leaf disease (Exobasidium vexans Massee) were significantly higher than those in susceptible cultivars, while the reverse was true for (-)-epigallocatechin gallate suggesting that epicatechin was involved in the resistance mechanism. The content of the methylxanthines, caffeine and theobromine in the leaf increased significantly in the initial translucent stage of the disease, probably as a defense response to fungal att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 16 publications
0
24
0
3
Order By: Relevance
“…These authors concluded that cultivar resistance is related to the amount of epicathechin in the avocado peel, and noted that fruit became susceptible to C. gloeosporioides during fruit ripening, when epicatechin levels decreased. In the same way, levels of (−)-epicatechin in tea cultivars resistant to blister blight leaf disease were significantly higher than those in susceptible cultivars (Punyasiri et al 2005), suggesting that epicatechin was involved in the resistance mechanism.…”
Section: Discussionmentioning
confidence: 73%
“…These authors concluded that cultivar resistance is related to the amount of epicathechin in the avocado peel, and noted that fruit became susceptible to C. gloeosporioides during fruit ripening, when epicatechin levels decreased. In the same way, levels of (−)-epicatechin in tea cultivars resistant to blister blight leaf disease were significantly higher than those in susceptible cultivars (Punyasiri et al 2005), suggesting that epicatechin was involved in the resistance mechanism.…”
Section: Discussionmentioning
confidence: 73%
“…For example, given that many plant secondary metabolites are putative defenses against pathogens and herbivores, predictions about allocation patterns for their production should reflect the selective pressures to which they are a response (Berenbaum 1995). Induction of caffeine and/or theobromine synthesis upon attack by fungal pathogens in tea (Camellia sinensis; Kumar et al 1995;Punyasiri et al 2005) and cacao (Theobroma cacao; Aneja and Gianfagna 2001), for example, provides evidence that selective agents may shape the production patterns of these alkaloids. Although plant nutrient concentrations have long been correlated with herbivore preferences (e.g., Mattson 1980), the effect of nitrogen availability on chemical responses to herbivores and pathogens has not been extensively explored.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of (2)-E (for epicatechin) in resistant cultivars are significantly higher than in susceptible ones, whereas the levels of EGCG in resistant cultivars are significantly lower than in susceptible ones. Epicatechin and EGC levels declined significantly in the infested areas of the leaf during blister blight infection, whereas the levels of ECG and EGCG increased at the translucent stage of the infection and declined on maturation of the blister (Punyasiri et al, 2005). Furthermore, infection of tea leaves susceptible to blister blight gave rise to a shift in the PA stereochemistry away from 2,3-trans (53% and 61% of the total starter and extension units of the PAs, respectively) toward 2,3-cis (26% and 40%, respectively; Nimal Punyasiri et al, 2004), and infection also resulted in increased gallic acid esterification of catechin and epicatechin.…”
mentioning
confidence: 91%